Driving Performance: Motivation, Facilities, and Safety in the Workplace: Meningkatkan Kinerja Karyawan: Pengaruh Motivasi, Fasilitas Kerja, dan Keselamatan dan Kesehatan Kerja - Tanti Krisnaningsih; Misti Hariasih (Academia Open, 2022)
This quantitative research study investigates the influence of motivation, work facilities, and occupational safety and health on employee performance at the Tulangan Sidoarjo District Office. Employing a saturated sampling technique, data was collected from 49 employees serving as respondents. The findings reveal that motivation, work facilities, and occupational safety and health each have a positive and partially significant impact on employee performance. Furthermore, when examined collectively, these factors exhibit a significant and positive influence on employee performance. These results underscore the importance of fostering motivation, providing adequate work facilities, and ensuring occupational safety and health measures to enhance employee performance. This research contributes to the existing body of knowledge in the field of organizational behavior and provides valuable implications for organizations seeking to optimize their employees' performance. Highlights: Motivation positively influences employee performance. Adequate work facilities contribute to improved employee performance. Ensuring occupational safety and health positively impacts employee performance. Keywords: Employee performance, Motivation, Work facilities, Occupational safety and health.